On π-Images of Locally Separable Metric Spaces - Tran Van An; Nguyen Van Dung (International Journal of Mathematics and Mathematical Sciences)
We characterize π-images of locally separable metric spaces by means of covers having π-property. As its application, we obtain characterizations of compact-covering (sequence-covering, pseudo-sequence-covering, and sequentially quotient) π-images of locally sparable metric spaces.